Composing images for video, film and photography - Luft, Greg; First Light Video Publishing (Venice, CA. : First Light Video Publishing, 2006)
This video gone through the process of analyze a scene, breaking down a scene, image selection concepts, the impact of camera angle, camera lens and also regarding the Lighting influence
Title from title screen
Narrator: Greg Luft
Keywords: Photography; Visual perception; Images, Photographic